Interaction of Russian and foreign education systems: The experience of the Department of Civil Procedure of Ural State Law University - V.V. Yarkov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The interaction between the Department of Civil Procedure of Ural State Law University and foreign partner universities has been discussed. Appealing to global practices is an ancient Russian tradition, which was supported by D.I. Meyer in particular. At the international level, the activity of the department embraces the following directions: training of researchers and teaching abroad; publishing of modern scientific literature on the problems of foreign law; participation in international scientific events. Within the first direction, international training of graduate students for getting the academic degrees of Candidate of Legal Sciences in Russia and Doctor of Law in France is performed. In the second direction, the issues of comparative and foreign law are included in the texts of educational literature, key foreign publications are translated, and educational and applied materials in the framework of international research and educational programs are prepared. The third direction involves presentations made by the department staff at international scientific conferences, their participation as experts in drafting of bills abroad, lecturing on a regular basis in foreign universities.